PROFESSIONAL TRAINING OF MASTERS OF MANAGEMENT FOR ACTIVITIES IN EXTREME CONDITIONS - Hladkova, Valentyna (Educological discourse, 2022)
The purpose of the article is to characterize the features of professional training of future managers in the field of education to work in extreme conditions. The main result of the training of future heads of educational institutions (managers of education) in the master’s degree is the formation of their professional competence. This integral quality of personality is manifested in the general ability and willingness to manage (especially in extreme conditions). Emphasis is placed on acmeological competence – the most important indicator of a high level of professionalism of management staff. In extreme conditions, a very important factor is the inherent nature of each manager (head of educational institution) of many acmeological invariants (managerial reflection, responsibility, empathy, professional optimism). Professional optimism is later transformed into public social optimism. Features of preparation of masters of management for educational branch are considered. In mastering the educational components, undergraduates use the acquired knowledge to implement acme-futuring – an effective tool for self-forecasting for the future. This is especially important in today’s extreme conditions. Future education managers develop author’s programs of personal and professional self-development and self-improvement. They are based not only on the top model of self-development, but also on the model of low self-development (tragic and anastrophic). These models emphasize the importance of taking into account the points of crisis and catharsis. In the educational process in the preparation of future masters of management in education is the development of professionalism of this category of specialists, improving their acmeological invariants, developing the ability to predict the future through the development of author’s programs of personal and professional self-development and self-improvement. Predicting one’s future confirms the manager’s own optimistic position. Optimism is a protective factor of the individual and society from distress and a significant factor in predicting subjective well-being. A person shows social activity, full of positive expectations for the future. By mastering this acme-energetic technology, the leader is able to help other people, his subordinates to gain confidence in the future. Accordingly, on this basis, social optimism is formed as a necessary condition for society to emerge from the crisis.